Earnings Management During Financial Crisis: The Case of Greece - Afroditi Ntokozi; Christos A. Tzovas; Constantinos G. Chalevas (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Did Greek listed firms engage in earnings management practices during the initial phase of the 2010's economic crisis? Motivation - Impact of structural attributes of a country along with firms' characteristics on economic entities' accounting policy decisions. Idea - Firms' accounting policy decisions are conditioned upon their characteristics and the conditions prevailing in the broader economic and business environment. We investigate whether these factors affect firms' propensity to engage in earnings management within a context of financial distress. Data - The sample consists of all Greek listed firms which were active for the period 2009-2014. Tools - We employ the Kothari et al (2005) model to estimate discretional accruals of Greek listed firms. Findings - The family-controlled Greek firms that are audited by Big-4 Auditing firms are likely to use discretionary accruals in order to affect accounting figures. This finding may be attributable to the family control of the firms, along with the weak legal enforcement and investor protection that prevail in Greece. In addition, discretionary accruals show a positive relation with firm's ability to cover its current liabilities using current assets while they are negatively associated with cash-flow from operations. Contribution - This study contributes to the existing literature on earnings management. Our research has been conducted in the initial phase of financial crisis and within an economic environment which is characterized by family-controlled firms, dependency on debt financing and low investor and creditor protection.
Keywords: M41; M42; 650; Earnings management; economic crisis; Big-4 auditor; cash-flows; leverage